Characterization and properties of singly and dually modified hydrogen peroxide oxidized and glutaraldehyde crosslinked biodegradable starch films - Prachayawarakorn, Jutarat; Kansanthia, Pornthip (My University, 2022)
Poor properties of native cassava starch film such as low mechanical properties and high water uptake are the limitations of biodegradable starch films. Dual modification is an alternative way to improve the properties. Characteristics and properties of oxidized, crosslinked and dually modified starch films by hydrogen peroxide oxidation and glutaraldehyde crosslinking were examined. Sequence of the dual modification was also studied. All starch films were prepared by casting technique using glycerol plasticizer. The oxidation and crosslinking of modified starch were confirmed by carbonyl and carboxyl contents as well as degree of crosslinking. The lowest and highest molecular weights of the modified starch were observed for the oxidized starch and crosslinked starch, respectively. Moreover, swelling power and moisture absorption of dually modified starch films was clearly lower than those of singly modified films. Additionally, both good stiffness and extensibility was also obtained from the dually modified films especially for the crosslinked-oxidized film. Moreover, thermal property and biodegradability were also determined.
Keywords: Biodegradable film; Mechanical properties; Modified starch